2019
DOI: 10.1111/sum.12517
|View full text |Cite
|
Sign up to set email alerts
|

How do hedgerows influence soil organic carbon stock in livestock‐grazed pasture?

Abstract: Hedgerows have the potential to influence ecosystem function in livestock‐grazed pasture. Despite this, they are often ignored when quantifying farmland ecosystem service delivery. In this study, we assess the contribution of hedgerows to the ecosystem function of carbon (C) storage, with a particular emphasis on soil organic carbon (SOC). We measured SOC stock (kg C m−2), on an equivalent soil mass basis, at 0–0.15 m depth in pasture adjacent to 38 hedgerows (biotic) and 16 stone walls or fences (abiotic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Therefore, it was not possible to account for differing bulk densities of the paired-plots and perform a mass correction for all data (Ellert and Bettany 1995). Due to higher SOC contents, the bulk densities under hedgerows were lower in all studies with reported bulk densities (Dhillon and Van Rees 2017;Ford et al 2019;Holden et al 2019;Paulsen and Bauer 2008;Thiel et al 2015). This could lead to an underestimation of mass-corrected SOC stocks in hedgerow soils compared with adjacent croplands.…”
Section: Soil Organic Carbon Stocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was not possible to account for differing bulk densities of the paired-plots and perform a mass correction for all data (Ellert and Bettany 1995). Due to higher SOC contents, the bulk densities under hedgerows were lower in all studies with reported bulk densities (Dhillon and Van Rees 2017;Ford et al 2019;Holden et al 2019;Paulsen and Bauer 2008;Thiel et al 2015). This could lead to an underestimation of mass-corrected SOC stocks in hedgerow soils compared with adjacent croplands.…”
Section: Soil Organic Carbon Stocksmentioning
confidence: 99%
“…The effect of hedgerow age on SOC storage is probably not visible due to an overlap with other influencing factors. In addition, Ford et al (2019) stated that hedgerows are often replanted where hedgerows once existed. Such land-use history could also blur the effect of hedgerow age on SOC.…”
Section: Soil Organic Carbon Stocksmentioning
confidence: 99%
“…Accurate quantification of SOC remains a challenge because of high spatial heterogeneity in soils. For instance, features such as hedgerows and fences can influence SOC due to their impact on soil moisture and bulk density (Ford et al, 2019). Soil compaction by agricultural machinery reduces macropores and creates water ponding (Mossadeghi-Björklund et al, 2019), which can affect SOC.…”
Section: Soil Organic Carbonmentioning
confidence: 99%
“…Soil cores (0.15 m deep, 0.05 m diameter) for the measurement of SOC stock were sampled once (during autumn) alongside each un-grazed sampling points for both the SW (n = 3) and the FD (n = 3) hedgerows. Soil cores were also collected in the grazed pasture at 1.2 m from the boundary fence of the SW and FD hedgerows as part of measurements published in Ford et al (2019). SOC concentration (g kg −1 of dry soil mass) was calculated using the conversion factor of 0.55 of SOM mass, with SOC stock (kg C m −2 ) of the 0-0.15 m depth re-calculated on an equivalent soil mass (ESM) basis, a layer of 1,000 t ha −1 as in Lee et al (2009); for a full description of the methods see Ford et al (2019).…”
Section: Estimation Of C Availabilitymentioning
confidence: 99%
“…The potential of existing and new farmland hedgerows, defined as lines of trees and shrubs typically managed by regular cutting (Baudry et al, 2000), to provide climate change mitigation via carbon (C) storage has been increasingly recognised over the past decade (Wolton et al, 2014;Scholefield et al, 2016). Despite this, accurate estimates of hedgerow C storage in temperate agroecosystems are rare, with both aboveand below-ground biomass (Thiel et al, 2015;Axe et al, 2017), soil CO2 efflux (Thiel et al, 2017) and soil organic carbon (SOC) storage (Amadi et al, 2016;Ford et al, 2019) largely unknown, or assessed in combination with other agroforestry systems (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%